DIRECT AND INDIRECT FOUNDATIONS, CHALLENGES, AND OPPORTUNITIES FOR IMPROVING LEXICAL COMPETENCE - Tilabova Gulnora Abdiaxatovna (Modern American Journals, 2025)
The article explores the direct and indirect foundations, challenges, and opportunities for improving lexical competence among learners of foreign languages, with a particular focus on German as a foreign language. Lexical competence, as a fundamental component of communicative competence, determines the learner’s ability to select, understand, and use appropriate vocabulary in various communicative contexts. The study emphasizes that lexical competence development depends on both direct approaches, such as explicit vocabulary instruction and semantic mapping, and indirect ones, such as extensive reading, immersion, and context-based learning. The research analyzes the psychological and linguistic mechanisms underlying vocabulary acquisition and retention, noting that motivation, frequency of exposure, and contextual richness play key roles. Furthermore, the study identifies common challenges faced by learners, including lexical interference, polysemy, idiomatic usage, and insufficient exposure to authentic language materials. Opportunities emerging from digital technologies, including AI-based translation tools, online corpora, and gamified learning platforms, are also examined as means of enhancing vocabulary mastery. The paper concludes that the integration of direct and indirect strategies provides an optimal framework for sustainable lexical development, enabling learners to achieve greater fluency, precision, and cultural awareness in foreign language communication.
Keywords: Lexical competence, direct learning, indirect learning, vocabulary acquisition, language teaching, linguistic challenges, digital learning, German language, communicative competence, pedagogy.